2022
DOI: 10.3389/fpls.2022.948742
|View full text |Cite
|
Sign up to set email alerts
|

Integrated analyses of transcriptome and metabolome provides new insights into the primary and secondary metabolism in response to nitrogen deficiency and soil compaction stress in peanut roots

Abstract: Peanut (Arachis hypogaea L.) is an important oil crop globally because of its high edible and economic value. However, its yield and quality are often restricted by certain soil factors, especially nitrogen (N) deficiency, and soil compaction. To explore the molecular mechanisms and metabolic basis behind the peanut response to N deficiency and soil compaction stresses, transcriptome and metabolome analyses of peanut root were carried out. The results showed that N deficiency and soil compaction stresses clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…In the current investigation, a set of genes involved in flavonoid and isoflavonoid biosynthesis were down-regulated simultaneously in the roots under the CP treatment (Figure 5). Similar results were also found in peanut roots subjected to compacted soil [18]. Whether these genes are inducements for the inhibition of root or nodule development or both needs further elucidation.…”
Section: Phenylpropanoid Lignin Flavonoid and Cell Wall Modification ...supporting
confidence: 72%
See 1 more Smart Citation
“…In the current investigation, a set of genes involved in flavonoid and isoflavonoid biosynthesis were down-regulated simultaneously in the roots under the CP treatment (Figure 5). Similar results were also found in peanut roots subjected to compacted soil [18]. Whether these genes are inducements for the inhibition of root or nodule development or both needs further elucidation.…”
Section: Phenylpropanoid Lignin Flavonoid and Cell Wall Modification ...supporting
confidence: 72%
“…Ethylene was supposed to orchestrate the AtFER-AtPIF3-AtPIEZO circuitry [17]. An integrated transcriptome and metabolome analysis of peanut root subjected to soil compaction revealed that differentially expressed genes (DEGs) and differentially accumulated metabolites related to soil compaction were mainly enriched in "oxidoreductase activity", "lipid metabolism" and "isoflavonoid biosynthesis" pathways [18]. Schneider et al [19] identified a root anatomical characteristic in maize, wheat and barley named multiseriate cortical sclerenchyma, which was formed upon exogenous ethylene exposure and associated with improved root tensile strength and increased penetration ability in compacted soils.…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids, including polyphenols, are secondary plant metabolites with antioxidant, anti-inflammatory, and cardioprotective effects (Birsa & Sarbu, 2022). Flavonoids also contribute to coping with stress in plants (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Integrated transcriptomic and metabolomic methods are increasingly being applied to reveal molecular mechanisms of environmental stress resistance in different crops based on genetic, physiological, and morphological data ( Bowne et al., 2011 ). This approach has led to the unraveling of the tolerance mechanism of wild soybean seedling roots to low-N stress ( Liu et al., 2020 ), identification of candidate genes possibly involved in oat adaptation to P deficiency ( Wang et al., 2018 ), elucidation of the response of rice carbon and N metabolism to high N ( Xin et al., 2019 ), understanding metabolic changes caused by regulation of P utilization efficiency in rice leaves ( Wasaki et al., 2003 ), regulation of phosphorylated metabolite metabolism in soybean roots in response to P deficiency ( Mo et al., 2019 ), effect of N deficiency on wheat grains during the medium filling stage ( Wang et al., 2021 ), response mechanisms of apple to different P stresses ( Sun et al., 2021 ), regulatory mechanisms of primary and secondary metabolism of peanut roots under N deficiency stress ( Yang et al., 2022 ), and the transcriptional and metabolic responses of maize buds to long-term K + deficiency ( Xiong et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%